2011
DOI: 10.1371/journal.pone.0016815
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Potentiates Caspase Independent Hydrogen Peroxide Induced Cell Death

Abstract: BackgroundThe pro-survival activity of NF-κB in response to a variety of stimuli has been extensively characterized. Although there have been a few reports addressing the pro-cell death role of NF-κB, the precise mechanism of NF-κB's pro-cell death function still remains elusive.Methodology/Principal FindingsIn the present study, we investigated the role of NF-κB in cell death induced by chronic insult with hydrogen peroxide (H2O2). Here, we show that NF-κB promotes H2O2 induced caspase independent but PARP de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Moreover, a PARP inhibitor was found to inhibit p38 expression and cause the phosphorylation of retinal neurons in mice model of chronic hypoperfusion and chorionic cells in chicks. 8,9 It has also been reported that inhibiting PARP could adjust p38 10 and that ERK phosphorylation of the MAPK pathway, could then downregulate nuclear factor (NF)-kB transcriptional 11 activity and consequently decrease the expressions of NF-kB-dependent genes such as intercellular cell adhesion molecule (ICAM-1), which is important during inflammatory processes. As, our previous results also demonstrated that inhibiting PARP could inhibit NF-kB activity in mice colon cancer CT26 cells; 12 vascular endothelial growth factor (VEGF), b-FGF (basic fibroblast growth factor), ICAM-1 and matrix metalloproteinases (MMP)-9 being well known NF-kB-dependent angiogenic-related factors, reflecting the relative migratory and proliferative ability of tumors were assessed in our experimental trial.…”
mentioning
confidence: 99%
“…Moreover, a PARP inhibitor was found to inhibit p38 expression and cause the phosphorylation of retinal neurons in mice model of chronic hypoperfusion and chorionic cells in chicks. 8,9 It has also been reported that inhibiting PARP could adjust p38 10 and that ERK phosphorylation of the MAPK pathway, could then downregulate nuclear factor (NF)-kB transcriptional 11 activity and consequently decrease the expressions of NF-kB-dependent genes such as intercellular cell adhesion molecule (ICAM-1), which is important during inflammatory processes. As, our previous results also demonstrated that inhibiting PARP could inhibit NF-kB activity in mice colon cancer CT26 cells; 12 vascular endothelial growth factor (VEGF), b-FGF (basic fibroblast growth factor), ICAM-1 and matrix metalloproteinases (MMP)-9 being well known NF-kB-dependent angiogenic-related factors, reflecting the relative migratory and proliferative ability of tumors were assessed in our experimental trial.…”
mentioning
confidence: 99%
“…Thus, taking in to account on the DNA damage induced by isothiacalothrixin B and subsequent arrest of cells in G1 and G2/M phase, without an increase in the protein levels of p53 strongly support the notion that the induction of cell death is p53- independent. Several studies have highlighted the p53-independent induction of cell death following DNA damage mediated through the pro-apoptotic p73 [ 43 , 44 ] or NF-kB (nuclear factor-kB) [ 45 , 46 ] or by the degradation of anti-apoptotic protein BCL2 [ 47 ], and thus it is possible that isothiacalothrixin B analogues caused cell death through any of these mechanisms. Both the thiacalothrixin B and calothrixin B induced accumulation of p21 waf1/cip1 protein.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] In the caspase-independent pathway, nuclear factor-kappa B (NF-κB), p53, p73 and orphan nuclear receptor Nur77 are reportedly involved in apoptosis. [33][34][35][36] One limitation of this study is the fact that it was conducted in vitro. Moreover, in a clinical setting, MTMP that is present in an infusion bag slowly enters the body in small amounts over an extended period of time.…”
Section: Discussionmentioning
confidence: 99%